An Infrastructure Based Worm Spreading Countermeasure for Vehicular Ad Hoc Networks - Zhang, Qi (Université d'Ottawa / University of Ottawa, 2017)
VANETs are the essential component of the intelligent transport system, which attract research and industrial interests increasingly. As the multifunctional mobile nodes integrating transporting, sensing, information processing, and wireless communication capabilities, vehicular nodes are facing remarkable security issues and more vulnerable to malware attack than conventional communication nodes. In this thesis, the behavior and the security issues of the worm spreading on VANETs are studied. The approaches of the worm spreading on VANETs are discussed and an infrastructure based worm containment strategy is proposed. The infrastructure based worm containment problem is modeled as minimum contamination problem by introducing the expected contamination degree. Then the existing greedy method is applied to solve the proposed problem in VANETs scenario. After that, the Grid-shrinking Greedy Method and the Simplified Greedy Method are proposed which incorporate the characteristics of road networks and VANETs respectively. Simulation results show the two proposed methods outperform the existing greedy method and the comparison method from both complexity and solution quality aspects.
Keywords: VANETs; Worm Spreading; Infrastructure Deployment; Minimum Contamination Problem